Spacetime algebraic skeleton - Aldrovandi, R. [UNESP]; Barbosa, A. L. [UNESP] (My University, 2003)
The cosmological constant is shown to have an algebraic meaning: it is essentially an eigenvalue of a Casimir invariant of the Lorentz group acting on the spaces tangent to every spacetime. This is found in the context of de Sitter spacetimes, for which the Einstein equation is a relation between operators. Nevertheless, the result brings to the foreground the skeleton algebraic structure underlying the geometry of general physical spacetimes, which differ from one another by the fleshening of that structure by different tetrad fields.